Phenomenology Study: Experiences Of Community Living Near A Road In Providing Help To Accident Victims - Vela Purnamasari; Nove Lestari; Nurul (Journal of Applied Nursing and Health, 2022)
Background: A phenomenon that often occurs in the community when a traffic accident occurs is that those who provide first aid (first responders) are mostly not medical officers but ordinary people around the scene. Of course, ordinary people will have unique and profound experiences that need to be explored to describe rescue actions when finding accident victims with all their limitations. Methods This study uses a qualitative design with an interpretive phenomenological approach to explore the meaning of the experiences of ordinary people who live close to the highway in assisting accident victims. Data saturation was achieved with 7 participants. The instrument in this research is the researcher as the core instrument, and other supporting tools in the form of a netbook equipped with a voice recording program (Camtasia studio ), ballpoint pen, and paper for field notes. Data collected through in depth interviews processed into transcripts and then analyzed using Interpretive Phenomenological Analysis (IPA) . Results: The results of the study found three major themes, namely trying to help victims as best they could, hoping for the best for victims and hoping for cooperation between the rescue team and the health care system. The three major themes are built from several sub-themes.. Conclusion: The conclusion is that people who live near highways will have the potential to become first responders in helping accident victims in the prehospital phase . With good cooperation between the general public and special lay parties and assisted by health services, it will greatly assist the process of first aid and follow-up assistance to accident victims, so that morbidity and mortality in accident victims can be minimized.